1990
DOI: 10.1055/s-0038-1647322
|View full text |Cite
|
Sign up to set email alerts
|

Use of Plasma with High Levels of lonised Calcium in the Production of Model Scale Goagulation Factor Concentrates

Abstract: SummaryWe have attempted to exploit the Ca2+ -dependent stability of factor VIII in producing factor VIII concentrates of higher yield. Plasma levels of ionised calcium were increased in two ways: (a) whole blood collection into half-strength citrate CPD anticoagulant, leading to free Ca2+ levels of ca 120 µM and (b) apheresis collection of plasma which was then recalcified to free Ca2+ levels of ca 300 µM under heparin cover. Coagulation factor concentrates were prepared using model versions of our industrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…It is important to note that citrate chelates Ca 2+ and Mg 2+ equally and incompletely, and that, at the citrate concentration used here, ≈30–70 μmol/l Ca 2+ should remain (Farrugia et al , 1990; Rebello et al , 2000) and, thus, about 25 μmol/l Mg 2+ . Binding to P‐selectin is Ca 2+ ‐dependent and optimal around 100 μmol/l for isolated leucocytes (Geng et al , 1992).…”
mentioning
confidence: 84%
“…It is important to note that citrate chelates Ca 2+ and Mg 2+ equally and incompletely, and that, at the citrate concentration used here, ≈30–70 μmol/l Ca 2+ should remain (Farrugia et al , 1990; Rebello et al , 2000) and, thus, about 25 μmol/l Mg 2+ . Binding to P‐selectin is Ca 2+ ‐dependent and optimal around 100 μmol/l for isolated leucocytes (Geng et al , 1992).…”
mentioning
confidence: 84%
“…enhancement in FVIII recovery is attributed to the fact that heparin maintains physiologic levels of calcium, which is an integral part of the FVIII molecule and important for its stability (Rock et al, 1979(Rock et al, , 1983Morgenthaler, Zuber & Friedli, 1985). Chelation of the calcium decreases the activity of FVIII that is not bound to vWF (Mikaelsson, Forsman & Oswaldsson, 1983;Rock et al, 1983;Farrugia et al, 1990). Also, in the presence of citrate, FVIII coagulant activity decreases during storage in a biphasic manner (Mikaelsson, Forsman & Oswaldsson, 1983) while collection of blood in heparin renders FVIII coagulant activity noticeably stable for at least 24 h (Krachmalnicoff & Thomas, 1983;Smit Sibinga et al, 1984;Morgenthaler, Zuber & Friedli, 1985;Cumming, Wensley & Delamore, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Factor VIII recoveries in cryoprecipitates prepared by fast-thaw and thaw siphon techniques or combined fast-thaw/thaw siphon techniques were improved by 20, 83 and 52%, re spectively, in 18-but not 3-hour old plasmas compared to standard citrate anticoagulated plasma. In studies by Farrugia et al [18], plasma recovered from full-and half strength CPD anticoagulant was initially frozen in liquid nitrogen and stored at -30 °C until cryoprecipitated using a stirred and heated vessel maintained at 0-2 °C. Factor VIITC yields were approximately 20% higher in half strength CPD plasma stored up to 6 h prior to freezing.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of fibrinopeptide-A generation [21,22] and the lack of effect of the thrombin inhibitors PPACK [23] and hirudin [24] on SP formation indicated that the process was thrombin-independent. However, SP forma tion was found to be associated with a reduction in the fibrinogen concentration of the thawed plasmas and the Palmer/Rosborough/Perkins/Bolton/ Rock/Ganz Heparinized Plasma Storage 268 [3,18,[57][58][59][60] used in order to preserve or restore and stabilize factor VIII activity. This study suggests that inhi bition of the generation of activated factor XIII or its effects on fibrinogen cross-linking has the potential for further improving factor VIII yields in such plasmas even under commercial freezing and storage conditions.…”
Section: Discussionmentioning
confidence: 99%